Pengaruh Penggunaan Active Knowledge Sharing terhadap Hasil Belajar Biologi Ditinjau dari Gaya Belajar Siswa Kelas X SMA Negeri Kebakkramat Tahun Pelajaran 2012/2013 - Anggrahini, Mardiayu; Maridi, Maridi; Ariyanto, Joko (BIO-PEDAGOGI, 2014)
This research is aimed to find out : (1) the effect of the implementation of Active Knowledge Sharing on student achievement in Biology at the grade of Class X at SMA Negeri Kebakkramat; (2) the  effect of students’ learning style on student achievement in Biology at the grade of Class X at SMA Negeri Kebakkramat; and (3) the interaction between learning strategy and learning style simultaneously on student achievement in Biology at the grade of Class X at SMA Negeri Kebakkramat. The research belonged to quasi experiment which use Posttest Only Non-Equivalent Control Group Design  while the students’ achievement in Biology was the dependent variable. The population of this research was all student of  Class X at SMA Negeri Kebakkramat in Academic Year 2012/2013. The sample of this research were the students of class X-1 as the control group and the students of class X-4 as the experimental group that were taken by cluster sampling. The data of the students’ achievement were completed by test, school documents, questionnaires and observation techniques. The analysis technique of this research was two away anava in different cell. The results of hypothesis testing strategies on student achievement is 0.000 for cognitive domains, 0.001 for affective domains, and 0.029 for psychomotor domains. The results of hypothesis testing learning style on student achievement is 0.179 for cognitive domains, 0.759 for affective domains, and 0.538 for psychomotor domains. The results of hypothesis testing of interaction strategies and learning styles on student achievement is 0.538 for cognitive domains, 0.716 for affective domain, 0,879 for psychomotor domains. The conclution of the research were 1) Active Knowledge Sharing strategy has significant effect toward biology’s student achievement of Class X at SMA Negeri Kebakkramat; 2)  Learning style does not have significant effect toward biology’s student achievement of Class X  at SMA Negeri Kebakkramat; 3) There is no  interaction between learning strategy and learning style toward biology’s student achievement of Class X  at SMA Negeri Kebakkramat. Key Words: Active Knowledge Sharing, Learning Style, Student Achievement In Biology